2021
DOI: 10.3390/vaccines9101095
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological and Economic Impact of a Cell-Based Quadrivalent Influenza Vaccine in Adults in the US: A Dynamic Modeling Approach

Abstract: Mutations of the H3N2 vaccine strain during the egg-based vaccine manufacturing process partly explain the suboptimal effectiveness of traditional seasonal influenza vaccines. Cell-based influenza vaccines improve antigenic match and vaccine effectiveness by avoiding such egg-adaptation. This study evaluated the public health and economic impact of a cell-based quadrivalent influenza vaccine (QIVc) in adults (18–64 years) compared to the standard egg-based quadrivalent influenza vaccine (QIVe) in the US. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…WTP threshold was CA$50,000 Replacing QIVe with QIVc in individuals 6 months–64 years of age (and aTIV with those ≥65 years of age) is cost-effective across varying assumptions of rVE and numbers of egg-adapted influenza seasons. Sensitivity analysis shows that this vaccine combination would be favorable in nearly all scenarios Nguyen et al, 2021 32 United States Adults 18–64 years of age Compared with QIVe for the entire population, the authors estimated the CE of QIVc in those 18–64 years of age Dynamic age-structured SEIR transmission model Societal 3 years QIVe = $17.22QIVc = $24.22 Hospitalization, GP visit Lostwork days US Dollar ($), year not reported QIVc versus QIVe was 26.8% (95% CI: 14–37) 26 Life years and QALYs lost were discounted PSA QIVc was dominant (ICER –$10,400/QALY). Base case scenario assumed 3 years of mismatch out of 5 years QIVc was more effective and cost-saving than QIVe, validated by sensitivity analyses Chi et al, 2023 33 Taiwan Children and adolescents 6 months–17 years of age Replacing QIVe with QIVc in children and adolescents 6 months–17 years of age 1-year age-stratified static decision tree Payer and societal perspective (two base case analyses) 1 year QIVc unit cost assumed 25% higher than QIVe Outpatient, ER visit, hospitalization, transportation costs Loss of productivity US Dollar ($), 2022 QIVc versus QIVe against all influenza strains was 8.1% 34 3% annualized inflation rate applied DSA and PSA ICER was $68,298/QALY and $40,085/QALY from payer and societal perspectives, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WTP threshold was CA$50,000 Replacing QIVe with QIVc in individuals 6 months–64 years of age (and aTIV with those ≥65 years of age) is cost-effective across varying assumptions of rVE and numbers of egg-adapted influenza seasons. Sensitivity analysis shows that this vaccine combination would be favorable in nearly all scenarios Nguyen et al, 2021 32 United States Adults 18–64 years of age Compared with QIVe for the entire population, the authors estimated the CE of QIVc in those 18–64 years of age Dynamic age-structured SEIR transmission model Societal 3 years QIVe = $17.22QIVc = $24.22 Hospitalization, GP visit Lostwork days US Dollar ($), year not reported QIVc versus QIVe was 26.8% (95% CI: 14–37) 26 Life years and QALYs lost were discounted PSA QIVc was dominant (ICER –$10,400/QALY). Base case scenario assumed 3 years of mismatch out of 5 years QIVc was more effective and cost-saving than QIVe, validated by sensitivity analyses Chi et al, 2023 33 Taiwan Children and adolescents 6 months–17 years of age Replacing QIVe with QIVc in children and adolescents 6 months–17 years of age 1-year age-stratified static decision tree Payer and societal perspective (two base case analyses) 1 year QIVc unit cost assumed 25% higher than QIVe Outpatient, ER visit, hospitalization, transportation costs Loss of productivity US Dollar ($), 2022 QIVc versus QIVe against all influenza strains was 8.1% 34 3% annualized inflation rate applied DSA and PSA ICER was $68,298/QALY and $40,085/QALY from payer and societal perspectives, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of rVE of QIVc versus QIVe applied in the CEA studies ranged from 8.1% to 36.2%, with a trend toward lower estimates applied in more recent CEAs. The three most recent CEAs used rVE data from meta-analysis estimates, 33–35 and several other analyses included a base case rVE point estimate originating from the 2017–2018 egg-adapted season 25 , 27 , 29 , 30 , 32 ( Table 2 ), which was characterized as a high-severity season with documented evidence of egg-adapted mutations in the egg-based vaccine A(H3N2) strain dominated by A(H3N2) and B strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-effectiveness of QIVc has been reported for the United States (US) [ 16 , 17 ], Spain [ 18 ], Brazil [ 19 ], the United Kingdom (UK) [ 20 ], and Germany [ 21 ]. In the UK, Kohli et al reported the cost-effectiveness of extending QIVc vaccination regimen from at-risk to low-risk adults between 50 and 64 years of age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation in this way promotes fewer instances of antigenic mismatch, raising vaccine efficacy. 4 The Pfizer-BioNTech (BNT162b2) COVID-19 vaccine was also approved for use in pediatric patients 5 to 18 years of age in 2021. Trials are still ongoing for pediatric patients 6 months through 4 years of age.…”
mentioning
confidence: 99%